2014
DOI: 10.1371/journal.pone.0094235
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Irisin with Metabolic Syndrome in Obese Chinese Adults

Abstract: Irisin, a recently identified novel myokine, drives brown-fat-like conversion of white adipose tissues and has been proposed to mediate beneficial effects of exercise on metabolism. Circulating irisin was significantly reduced in type 2 diabetes patients; however, no evidence is available about its association with metabolic syndrome (MetS) and effects of adiposity and muscle mass on circulating irisin have been controversial. Cross-sectional data on socio-demographic, lifestyle, clinical characteristics and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
151
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(182 citation statements)
references
References 22 publications
25
151
5
1
Order By: Relevance
“…It is conceivable that this association has a direct and/or indirect effect on the endothelial dysfunction in patients with type 2 diabetes. Besides, it has been suggested that waist circumference, fast insulin, FBG and 2-h BG, are related to serum irisin levels (Yan et al, 2014). Our findings indicate similar results.…”
Section: Discussionsupporting
confidence: 88%
“…It is conceivable that this association has a direct and/or indirect effect on the endothelial dysfunction in patients with type 2 diabetes. Besides, it has been suggested that waist circumference, fast insulin, FBG and 2-h BG, are related to serum irisin levels (Yan et al, 2014). Our findings indicate similar results.…”
Section: Discussionsupporting
confidence: 88%
“…We did not found any study examining the relation between irisin and HbA1c in T1DM patients. However, in studies conducted with patients with the T2DM and metabolic syndromein contrast with our study -irisin levels were negatively correlated with HbA1c (Choi et al 2013;Yan et al 2014). Th is relation between irisin and HbA1c have not been interpreted in these studies.…”
Section: Discussioncontrasting
confidence: 88%
“…Notably, within NAFLD group, those with mild steatosis had higher irisin levels than NAFLD patients with moderate-to-severe steatosis. It is also of interest that similar irisin levels were observed between obese in non-obese individuals, or between individuals with and without metabolic syndrome in this study [31], contrary to other studies showing increased [32] or decreased [33] irisin levels in individuals with metabolic syndrome. Choi et al speculated that irisin increases in early steatosis, as a compensatory mechanism to limit it, but if the mechanism fails and steatosis progresses, irisin decreases [31].…”
Section: Clinical Studiessupporting
confidence: 62%